2011
DOI: 10.1037/a0023927
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic dissociation and experiential avoidance as prospective predictors of posttraumatic stress symptoms.

Abstract: Peritraumatic dissociation (PD) and experiential avoidance (EA) have been implicated in the etiology of posttraumatic stress symptomatology (PTSS); however, the function of these two factors in the onset and maintenance of PTSS following a potentially traumatic event is unclear. The temporal relationships between EA, PD, and the four clusters of PTSS proposed by the Simms/Watson dysphoria model (Simms, Watson, & Doebbeling, 2002) were examined in a three-wave prospective investigation of 532 undergraduate wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
112
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 68 publications
16
112
0
Order By: Relevance
“…AAQ-II scores have been uniquely predictive of PTSD severity in cross-sectional research with a subset of the current sample (Meyer, Morissette, Kimbrel, Kruse, & Gulliver, 2013) and in prospective research with college students exposed to a campus shooting (Kumpula, Orcutt, Bardeen, & Varkovitzky, 2011). Internal consistency was .94 in the current study.…”
Section: Measures Of Psychological Resources and Mediating Variablesmentioning
confidence: 48%
“…AAQ-II scores have been uniquely predictive of PTSD severity in cross-sectional research with a subset of the current sample (Meyer, Morissette, Kimbrel, Kruse, & Gulliver, 2013) and in prospective research with college students exposed to a campus shooting (Kumpula, Orcutt, Bardeen, & Varkovitzky, 2011). Internal consistency was .94 in the current study.…”
Section: Measures Of Psychological Resources and Mediating Variablesmentioning
confidence: 48%
“…In fact, high levels of EA measured prior to a traumatic event predict increased PTS symptoms in the acute aftermath of the event and 8 months later (Kumpula et al 2011), thus providing temporal evidence of EA as a risk factor for the development of PTS.…”
Section: Pts-related Individual Difference Factorsmentioning
confidence: 94%
“…Dissociative symptoms may not only be an integral part of PTSD symptomatology (Dalenberg & Carlson, 2012), they may also be independent mechanisms for coping with overwhelming emotions (Kumpula, Orcutt, Bardeen, & Varkovitzky, 2011). This is consistent with this notion of peritraumatic dissociation, which is conceptualized as a coping mechanism (Kumpula et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…in civilian populations exposed to mass shootings (Kumpula et al, 2011) or motor vehicle accidents (Ehlers, Mayou, & Bryant, 1998) and in combat veterans (Bremner et al, 1992; Marmar et al, 1994). However, a prospective longitudinal study showed that peritraumatic dissociation was no longer predictive of PTSD symptom severity at follow-up after controlling for PTSD symptom severity, measured within days of exposure (Marshall & Schell, 2002).…”
Section: Introductionmentioning
confidence: 99%